2015
DOI: 10.1371/journal.pone.0139802
|View full text |Cite
|
Sign up to set email alerts
|

Linking Intertidal and Subtidal Food Webs: Consumer-Mediated Transport of Intertidal Benthic Microalgal Carbon

Abstract: We examined stable carbon and nitrogen isotope ratios for a large variety of consumers in intertidal and subtidal habitats, and their potential primary food sources [i.e., microphytobenthos (MPB), phytoplankton, and Phragmites australis] in a coastal bay system, Yeoja Bay of Korea, to test the hypothesis that the transfer of intertidal MPB-derived organic carbon to the subtidal food web can be mediated by motile consumers. Compared to a narrow δ13C range (−18 to −16‰) of offshore consumers, a broad δ13C range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
23
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 58 publications
(97 reference statements)
7
23
2
Order By: Relevance
“…This is consistent with other ontogenetic dietary shifts observed in California killifish, such as changes in prey types, prey sizes, prey abundance, and microhabitat use with time [85,86]. These fish may, in turn, be important vectors for transferring small plastics and contaminants to the broader coastal food web given their abundance, their roles in connecting intertidal with both subtidal and terrestrial ecosystems, and their roles as forage fish for many species [92][93][94][95]. While examples of the transfer of plastics between trophic levels are on the rise [30][31][32][33], needed is a better understanding of the mechanisms underlying the pathways of…”
Section: Natural History and Contamination Risk In Fishsupporting
confidence: 78%
“…This is consistent with other ontogenetic dietary shifts observed in California killifish, such as changes in prey types, prey sizes, prey abundance, and microhabitat use with time [85,86]. These fish may, in turn, be important vectors for transferring small plastics and contaminants to the broader coastal food web given their abundance, their roles in connecting intertidal with both subtidal and terrestrial ecosystems, and their roles as forage fish for many species [92][93][94][95]. While examples of the transfer of plastics between trophic levels are on the rise [30][31][32][33], needed is a better understanding of the mechanisms underlying the pathways of…”
Section: Natural History and Contamination Risk In Fishsupporting
confidence: 78%
“…Site‐specific values for measured plant variables are given in Table S2. Due to lack of in situ sampling of phytoplankton at the sites, δ 13 C values from the literature were used in the stable isotope analysis (Conway‐Cranos et al, ; Goering et al, ; Jorgensen et al, ; Kang et al, ; Kajihara et al, ; Miyajima et al, ; Pernet et al, ; Röhr et al, ; Tagliabue & Bopp, ; Tiselius & Fransson, ). The δ 13 C values for plankton selected from the literature for each site and used in the analysis are given in Table S3.…”
Section: Methodsmentioning
confidence: 99%
“…Benthic microalgae and kelp have a higher carbon isotopic ratio than phytoplankton which could be a possible carbon source at the base of the echinoderm food chain (France, 1995). Bioturbation of refractory organic matter (poorly biodegradable leftovers of organisms) in the sediment could also cause an enrichment of δ 13 C if consumed by benthic primary consumers (Nadon and Himmelman, 2006), (Kang et al, 2015). It can be concluded that the more complex and pelagic the food web, the more degraded material reaches the sea floor.…”
Section: Benthic and Demersal Invertebratesmentioning
confidence: 99%